Factors affecting the selection process to treatment gold complex minerals - Azañero Ortiz, Angel (2009)
The need to develop and know methods for metallurgical treatment to process gold-bearing refractory minerals or hard to treat be- cause of carbon contents, tellurium, antimony, arsenic, carbonates and gold in solution solid sulfides, forces us to study the different methods of specific oxidation that should be applied in each mineral before to leach ore to reach high recoveries into precious metals Through Gravimetrically followed by cyanidation is obtained 94.74% of gold extract in the studied mineral.